Pengaruh Getaran Tanah Akibat Peledakaan Terhadap Kemantapan Lereng Tambang Air Laya Selatan PT Bukit Asam (Persero) Tbk - Nur Amaliya; Mardiah Mardiah; Abrianto Akuan (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2016)
Rock blasting operation generate deformation as a result of the vibration that will destruct rockmass and cause slope failure to endager the human safety. There are so many geological structuressuch as fault, joint and structures that caused the failure slope in South Air Laya Mine Site. Thereforeit is necessary to conduct a research of the influence of blast vibration on slope stability factor aroundthe area. Stability factor value (FK) was obtained from calculation of Geolsope 2007. Test ofPhysical and mechanical parameter valueincluded value of weight content of soil / rock (w) withkn/m3unit, cohesion (C), shear angle(), plasticity index value (IP) as well as the compressivestrenght (UCS). Vibration value was obtained from the measurement of vibration using BlasmateIII.Vibration value used is Peak Acceleration Tranverse (the greatest point taken). Furthermore, physicaland mechanical parameters data of rock and vibration was processed by using Geoslope2007software.Based on research conducted for 50 days by blasting as many as 15 times. Vibration valueused is 3 vibration greatest value, namely 0.102 g; 0.086 g and 0.084 g.The calculation of slope FKvalue using Geoslope2007 software was obtained the comparison between slope FK before and afterblasting. Slope FK value before blasting was 3,744 to 4,058 and slope FK after blasting was 3,422 to2,783. From the overall of slope FK value, slope in blasting area was conluded in safe category (FK >1,25).